Physical Exercise of Primary and Middle School Students From the Perspective of Educational Psychology and Parents’ Entrepreneurship Education - Song, Chao; Ge, Sha; Xue, Jingjing; Yao, Wanxiang (Frontiers in Psychology, 2022)
The study aims to help primary and secondary school students develop a good habit of physical exercise by exploring the current situation of physical exercise of primary and secondary school students and analyzing the factors affecting their physical exercise. Then, intervention strategies are figured out for different groups of students and help them develop a good habit of physical exercise. From the perspective of educational psychology and parents’ entrepreneurship education, the research on the physical exercise of primary and secondary school students is conducted by a questionnaire survey, mathematical statistics and literature review. A total of 280 students from five schools in Tianjin are selected as the research subjects, and the current situation of students’ physical exercise in these five schools is investigated. The results show that 40.5% of boys and 39.4% of girls can take physical exercise more than three times a week; 48.9% of the students do physical exercise for more than 30 minutes each time; the students who usually take regular exercise at school account for 82.1%. The physical exercise that students always do is running, badminton and table tennis, which rank the top three among the sports they do. The students usually play basketball, volleyball and football, and they rarely do the sports like swimming, Wushu, and aerobics. This result is closely related to the characteristics and places of primary and middle school students. The survey shows that the physical exercise awareness of most primary and secondary school students is correct; most students can participate in physical exercise, but few students can do it regularly; parents’ support, parents’ habits of doing exercise, and family’s spending on physical exercise have a significant impact on developing students' habits of doing physical exercise. Based on the above, it is concluded that the primary and secondary stage is very important for students. Physical education teachers should follow the principle of teaching different students with different methods, enrich teaching materials, and improve teaching quality. The study provides a reference for the reform of PE to guide primary and middle school students to participate in sports activities, improving students’ physical quality.